A pooled job physical exposure dataset from multiple independent studies in a consortium study of carpal tunnel syndrome - Bao, Stephen S. (Occup Environ Med, 2014)
BACKGROUND: Six research groups independently conducted prospective studies of carpal tunnel syndrome (CTS) incidence in 54 US workplaces in 10 US States. Physical exposure variables were collected by all research groups at the individual worker level. Data from these research groups were pooled to increase the exposure spectrum and statistical power. OBJECTIVE: This paper provides a detailed description of the characteristics of the pooled physical exposure variables and the source data information from the individual research studies. METHODS: Physical exposure data were inspected and prepared by each of the individual research studies according to detailed instructions provided by an exposure sub-committee of the research consortium. Descriptive analyses were performed on the pooled physical exposure dataset. Correlation analyses were performed among exposure variables estimating similar exposure aspects. RESULTS: At baseline, there were a total of 3010 subjects in the pooled physical exposure dataset. Overall, the pooled data meaningfully increased the spectra of most exposure variables. The increased spectra were due to the wider range in exposure data of different jobs provided by the research studies. The correlations between variables estimating similar exposure aspects showed different patterns among data provided by the research studies. CONCLUSIONS: The increased spectra of the physical exposure variables among the data pooled likely improved the possibility of detecting potential associations between these physical exposure variables and CTS incidence. It is also recognized that methods need to be developed for general use by all researchers for standardization of physical exposure variable definition, data collection, processing and reduction.